Prácticas de enseñanza de Lengua en segundo año de educación general básica en una Institución Educativa ubicada en la parroquia de San Antonio del Distrito Metropolitano de Quito - Acosta Mena, Sara Alexandra (2016)
The goal of this case study is to investigate the educational practices, difficulties and development of pedagogical techniques in the language area, second year, parallels A and B of a school located in San Antonio de Pichincha Parish, Metropolitan District of Quito. In recent years Ecuador has emphasized the development of linguistic intelligence in elementary school. To achieve this result, it is required strengthening teaching practices in the daily life of the classroom, a work with a complex dynamic where multiple factors influence its development. Therefore it becomes imperative to analyze and contribute with input, in order to achieve the objectives and improve the quality of education. This time, our methodology has made intensive use of qualitative research following the ethnographical method. Recurring to observation and interviews, we were able to obtain significant data concerning different elements relevant to the pedagogical practices under scrutiny. It was possible to save information about methodological conceptions, ways of planning, modes of structuring the contents, about the role of the teacher to meet tasks and asses strategies, as well as about different modes of distribution of time, space, resources and interaction between teachers and students in the classroom.